Craftspeople and Designer Makers in the Contemporary Creative Economy - Luckman, Susan (Creative Working Lives, 2020)
This open access book explores the experience of working as a craftsperson or designer maker in the contemporary creative economy. The authors utilise evidence from the only major empirical study to explore the skills required and the challenges facing contemporary makers in an increasingly crowded marketplace. Drawing upon 180 interviews with peak organisations, established and emerging makers, and four years of fieldwork across Australia, this book offers a unique insight into the motivations informing those who seek to make an income from their craft or designer maker practice, as well as the challenges and opportunities facing them as they do so at this time of renewed interest internationally in the artisanal and handmade. Offering a rich and deep collection of real-life experiences, this book is aimed both at an academic and practitioner audience.